PERTANGGUNGJAWABAN PIDANA SEORANG PENYIDIK KEPOLISIAN TERHADAP BARANG BUKTI YANG DISITA PERSPEKTIF KITAB UNDANG-UNDANG HUKUM ACARA PIDANA - TITIN APRIANI (Universitas Mahasaraswati K. Mataram, 2022)
The purpose of this study is to find out how the criminal responsibility of a police investigator for the confiscated evidence and how the sanctions are given to members of the investigator who misuse the evidence. This research is alibrary research that uses data in the form of books, laws, articles, journals and other literature related to the title, while the technique and data collection is to collect various ideas, theories and concepts from various literatures that focus on the process. comparison between arguments, articles or other laws. The approach method used in this research are the statutory approach and the conceptual approach approaches). The results of the study indicate that the responsibility for the evidence by investigators who misuse the evidence can be sanctioned for violating the professional code of ethics and can be prosecuted with appropriate criminal penalties.